MON-643 Diabetes’ Cost to Us Taxpayers: Thirty-Day Readmission and Resource Utilization Among Diabetics Patients Admitted with ST-Elevation Myocardial Infarction: A Propensity Score Match Analysis - Nasserifar, Shabnam (J Endocr Soc, 2020)
PURPOSE: To determine the relationship between diabetes and thirty-days readmission, mortality, morbidity, and health care resource utilization in patients who were admitted with ST-Elevation Myocardial Infarction (STEMI) in the United States. METHOD: A retrospective study was conducted using the AHRQ-HCUP Nationwide Readmission Database for the year 2014. Adults (≥ 18 years) with a primary diagnosis of STEMI (1), along with a secondary diagnosis of diabetes were identified using ICD-9 codes as described in the literature (2). The primary outcome was the rate of all-cause readmission within 30 days of discharge. Secondary outcomes were reasons for readmission, readmission mortality rate, morbidity, and resource use (length of stay and total hospitalization costs and charges). Propensity score (PS) using the 1:1 nearest neighbor matching without replacement was utilized to adjust for confounders (3). Independent risk factors for readmission were identified using a Cox proportional hazards model (4). RESULTS: In total, 116,124 hospital admissions among adults with a primary diagnosis of STEMI were identified, of which 18.05% were diabetics. 1:1 PS matching was performed based on demographic (age, gender, hospital status, etc.) and clinical characteristics (Charlson comorbidity score. The 30-day rate of readmission among diabetics and non-diabetics with STEMI were 9.31% vs. 6.18% (p <0.001). The most common readmission for both groups was recurrent myocardial infarction. During the index admission for STEMI, the length of stay (LOS) among diabetics and non-diabetics patients were not statistically different (4.74 vs 4.58 days, p=0.12). However, the total hospital cost for the diabetic patients was statistically different ($27,027 vs $24,807, p <0.001). Most importantly, diabetics patients’ in-hospital mortality rate during their index admission was significant higher (10.20% vs 5.92%, p <0.001). Amongst those readmitted, the LOS, total hospital cost, or in-hospital mortality among diabetics were not statistically different when compared to their counterparts during their readmission. Diabetes (HR 1.60, CI 1.27-2.02, p <0.001) was an independent predictor associated with higher risks of readmission. Other independent predictors associated with increased 30-day readmission include acute exacerbation of CHF, acute exacerbation of COPD, acute kidney injury, secondary diagnosis of pneumonia, history of COPD, history of ischemic stroke, history of atrial fibrillation & atrial flutter, history of chronic kidney disease, history of iron deficiency, and use of mechanical ventilator. CONCLUSION: In this study, diabetics patients admitted with STEMI have a higher 30 days of readmission rate, total hospital cost, and in-hospital mortality (p <0.001) than their non-diabetic counterparts.